MANAJEMEN PROYEK PELAKSANAAN RENOVASI LAPANGAN STADION SAPTA MARGA AKMIL - Situmorang, Rivo Samuel A; Agung Prapsetyo; M. Zain Triputra; Budi Mawardi Syam (JURNAL TEKNIK SIPIL PERTAHANAN, 2023)
The Military Academy is an educational institution located in the City of Magelang, Central Java. The facilities provided at educational institutions are very diverse, including the Athletic Stadium where there is a jogging track. The existing jogging track has many benefits that can be utilized, including physical training and especially for cadets, parenting coaching. Therefore, a jogging track renovation was carried out which previously did not meet the standards of the IAAF (International Amateur Athletic Federation) until now it has met class 2 standards. The purpose of this study was to see the results of carrying out the renovation until it was completed and met the target whether it was in accordance with the IAAF itself or not This research is a qualitative research. The data sources in this study were primary data obtained through in-depth interviews with Zeni Akmil staff, Kazi AKMIL, documentation and observation of the facilities at the Sapta Marga Akmil stadium jogging track. While secondary data comes from literature and journals that support the completion of this Final Project, with SWOT analysis in the discussion. The results of this study are the current conditions of the Sapta Marga Akmil stadium jogging track against the standards set by the IAAF (International Amateur Athletic Federation).